Crystallography of protein dynamics - Ando, Nozomi (Methods in enzymology, 2023)
Crystallography of Protein Dynamics, Volume 688, the latest release in this important series, highlights new advances in the field, with this new volume presenting interesting chapters written by an international board of authors.